Onion Growth, Yield and Quality as Influenced by Planting Time and Seedling Age - VPS PANGHAL; AXAY BHUKER; DS DUHAN; AMIT KUMAR (Seed Research, 2026)
The production of quality onion bulb is very important for producing the quality seed in the next season. Consequently, the experiment was conducted on sandy loam soil at CCS Haryana Agricultural University, Hisar during winter season of 2014-15 and 2015-16 with nine treatments combinations viz., three transplanting dates and three age of seedlings planted in a Factorial Randomized Block Design with three replications. Maximum plant height (68.4 cm), number of leaves per plant (8.2) and bulb yield (310.8 q/ha) was recorded in 30th December transplanted crop as compared to other transplanting dates. However, bulb quality parameters like neck thickness (9.64 mm), bolting (1.20%) and split bulb (5.2%) were noticed significantly minimum with delayed transplanting on 15th January as compared to earlier date. There was no significant difference recorded between 50 and 60 days old seedlings for plant height, number of leaves and bulb yield, however, these parameters were maximum as compared to 70 days old seedlings, while, neck thickness of bulb, bolting and split bulb percentage were recorded minimum. So it is concluded that in semi-arid, sub tropical region of north western India particularly in Haryana state, 50 to 60 days old seedlings planted on 30th of December produced higher yield and quality bulb of onion.